Nitrogen Distribution in Annual Growth of ‘Italia’ Table Grape Vines - Ferrara, Giuseppe; Malerba, Anna Daniela; Matarrese, Angela Maria Stella; Mondelli, Donato; Mazzeo, Andrea (Frontiers in Plant Science, 2018)
Little information is available about either nitrogen (N) content/concentration in table grape vines. The knowledge about N accumulated by the vine organs during the season could support sustainable fertilization programs for table grape vineyards. The aim of the present paper was to investigate the N content in different annual organs, in summer and winter pruning materials, clusters at harvest and fallen leaves at post-harvest of table grape vines in order to verify the vine annual N requirements to be used for sustainable N fertilization schedules. Biomass and nitrogen were analyzed at six phenological growth stages (flowering, berry-set, berry growth, veraison, ripening, and harvest) from 2012 to 2015. N concentration (>40 g/kg d.w.) was highest in the leaves of the secondary shoots at flowering, whereas values >30 g/kg were measured in the leaves of the primary shoots. N concentration in the clusters at harvest was 5.3-7.6 g/kg with an accumulation of 18.6-25.4 g/vine in the 3 years. The decrease of N content in the primary leaves after flowering indicated a remobilization towards the clusters, which acted as a stronger sink. Later in the season (veraison-ripening), leaves translocated N to permanent organs such as primary stems. Pruning wood and fallen leaves accounted for the largest N removal from the vineyard after clusters, 6.0-7.9 and 9.2-10.2 g/vine, respectively. With regards of the vine annual biomass, the growth followed a sigmoidal model reaching 7300-7500 g of d.w at harvest. Vine leaf area reached the highest surface at veraison (17-21 m2), taking into account both primary and secondary leaves. Vines accumulated 35 g/vine of N at harvest, not considering the N removed with the intense summer pruning practices (7 g/vine) and the fraction mobilized towards the storage organs (10-15 g/vine). The overall N required by the vine was around 50-55 g/vine, which corresponds to 80 kg of N/ha in a vineyard with 1500 vines and a yield of 40 t/ha. Summer and winter pruning practices removed 29-31 g/vine of N which will be partly available (to be considered in the fertilization schedule) for the vine in the successive years if incorporated and mineralized in the